2023
DOI: 10.31893/jabb.23004
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of avian species, their ecosystems and climate conditions in two zones of High Atlas (central Morocco) for ecotouristic purposes

Abstract: The analysis of avian diversity and their natural ecosystems at a regional scale is the first step to understanding and classifying a specific region's ecological importance and, therefore, adopting sustainable economic activities and implementing suitable conservation measures. This study investigated the avian richness and natural ecosystems in Eastern and central High Atlas between 2015 and 2021. Transects and point-count methods were used to identify and estimate populations of birds and to delimit the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Te authors have recorded 92 breeding birds in spring and summer in 2018 and 2019. Equally, Mansouri et al [77] and Wakass et al [78] documented 98 breeding species in the spring and summer seasons in the east of High Atlas near Midelt, which is only about 120 km from our study area.…”
Section: Discussionmentioning
confidence: 70%
“…Te authors have recorded 92 breeding birds in spring and summer in 2018 and 2019. Equally, Mansouri et al [77] and Wakass et al [78] documented 98 breeding species in the spring and summer seasons in the east of High Atlas near Midelt, which is only about 120 km from our study area.…”
Section: Discussionmentioning
confidence: 70%
“…arenicola, with 23.57% of nests, and T. merula, with 20.95% of nests. Currently, (Mansouri et al 2021c;Wakass et al 2023) mention the presence of H. polyglotta as a breeder in the upper Moulouya and Eastern High Atlas (15 km to Upper Moulouya), while (Mounir et al 2022) record the breeding pairs of this small passerine in the Central High Atlas (150 km to the Upper Moulouya). However, none of these authors have recorded nests of this species in Morocco or North Africa.…”
Section: Discissionmentioning
confidence: 99%
“…In Morocco, many studies have reported the ecological landscapes with potential ecotouristic activities. Wakass et al (2023bWakass et al ( , 2023a reported the existence of geosite structures with abundant animal species in Central and Eastern High Atlas. In El Ksiba belonging to Beni Mellal region (Central Morocco), a heritage of Travertine Waterfall Geosites was described for conservation purposes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the physical landscapes, living organisms have received little interests in these areas. Wakass et al (2023b) mentioned the existence of 175 avian species including 20 birds with ecotouristic interests. These animal and vegetation species constitute with their ecosystems a unique unit that needs more interest in order to ensure its sustainability.…”
Section: Introductionmentioning
confidence: 99%